ENTRE EL SAINETE Y LA IMPRENTA: ANA BENÍTEZ, VIUDA DE GONZÁLEZ DEL CASTILLO Y VIUDA DE COMES - Beatriz Sánchez Hita (Cuadernos de Ilustración y Romanticismo, 2018)
The printing house called «de la viuda de Comes [the widow of Comes in English]» —associated with Ana Benítez— operated in Cadiz from 1808 to, at least, 1843. This research retrieves the production of this printing house, determining the periods of printing activity and paying special attention to its work during the War of Independence. During this period, Ana Benitez published in the printing house of Manuel Comes twenty-one sainetes written by her first husband: Juan Ignacio González del Castillo. This production, along with the twenty sainetes edited by Francisco de Paula Periu in Isla de León represented the first complete edition of the sainetes by González del Castillo. The present study demonstrates that this edition has special interest, since it was produced under the supervision of his widow and probably using the author’s original manuscripts.